Narrative Therapy Training to Improve the Skills of Companions in Handling Victims of Violence Against Women - Suwatah, Suwatah; Amriana, Amriana; Fanan, M. Athoiful; Putri, Rahmah Widya (Jurusan Bimbingan dan Konseling Islam, 2023)
The aim of this training activity is to improve the skills of accompanying victims of violence against women. The method used is qualitative with a case study design. Research subjects are those who are involved in the activities studied, understand and know information related to this research. Based on this, the research subjects in this study were selected using the following criteria: (1) Narrative therapy training participants. (2) Participants who take part in narrative training from start to finish and are willing to be interviewed. The data collection techniques used in this research are observation, interviews and documentation. The results obtained are that there are 9 stages in narrative therapy which include: (1) delivery of material; (2) participant grouping; (3) participants discuss the review of narrative therapy and the cases they each bring; (4) group members discuss the review of narrative therapy material that will be presented. Then the results of the discussion are written on flipchart paper to be presented later; (5) participants are asked to dissect the initial manuscript. The initial manuscript was dissected and the root of the problem was looked for; (6) narrative therapy training participants were asked to deconstruct the initial script that they had analyzed on the first day; (7) participants are directed to discuss unique outcomes and reconstruct competing narratives; (8) outcomes, assembling unique outcomes into new narratives, and strengthening new narratives; (9) The presenter interrupted the participants to express their impressions during the narrative therapy .